The Role of Customer Service and Promotions in Shaping Consumer Preferences for Motorcycle Accessories - Sujarittanonta, Pacharasut (Journal of Policy Options, 2021)
With nearly ten percent of the world's motorcycles in use in Thailand, the country represents a significant market for motorcycle accessories. This pilot qualitative research seeks to explore consumer insights using completion techniques, specifically sentence completion and story completion. Three respondents were selected through accidental sampling, recruited as they entered a motorcycle accessory shop. The respondents, all male and at least 15 years old, completed questionnaires that aimed to uncover their perceptions, preferences, and motivations regarding motorcycle accessories. This study provides preliminary insights into consumer behavior in Thailand’s large and growing motorcycle accessory market. This research was conducted in a motorcycle accessory shop located in the Northeastern part of Thailand, an area selected due to its conducive environment for conducting such studies. The story completion test results revealed that all participants were willing to participate in a promotion offering a ten percent discount to membership card holders. Additionally, it was found that the participants had visited the motorcycle accessory shop based on recommendations from friends, reflecting the strong influence of positive word-of-mouth in shaping their purchasing decisions. This highlights the importance of social influence and promotions in attracting customers to the shop. Furthermore, the research revealed that consumers highly value the knowledge and assistance provided by sellers, particularly when it comes to receiving advice on which motorcycle accessories would best suit their needs. This personal interaction significantly enhances customer satisfaction, as it ensures that buyers feel supported in their purchasing decisions. Equally important is the provision of quality after-sales service, which reassures consumers that they can rely on the shop for continued support, fostering long-term customer loyalty and repeat business. These factors indicate that customer service and relationship management play a crucial role in the motorcycle accessory market, alongside the products themselves. However, it is important to recognize that this study was merely a pilot qualitative research project, conducted to provide initial insights and serve as a foundation for more comprehensive future studies. The limited sample size, consisting of only three respondents, means that the results, while useful for exploratory purposes, are not representative of the broader market. Therefore, to improve the validity and generalizability of the findings, future research should involve a significantly larger sample size. Expanding the sample would allow researchers to capture a more accurate reflection of consumer behavior, preferences, and market dynamics across different regions and demographics. In addition, while qualitative research methods such as completion techniques are useful for gaining deep insights into consumer psychology and motivations, the inclusion of quantitative research is highly recommended for future studies. Quantitative research, involving a larger number of participants, would provide a more statistically reliable analysis of consumer trends, preferences, and behaviors. This approach would be especially valuable when studying a few hundred or more accessory buyers, enabling researchers to identify key patterns and correlations that can guide marketing strategies and product development in the motorcycle accessory market. By combining qualitative insights with quantitative data, future studies could offer a more comprehensive understanding of consumer needs and expectations. This would allow businesses in the motorcycle accessory industry to develop more targeted marketing campaigns, refine their product offerings, and improve customer service strategies, ultimately leading to increased sales and stronger customer relationships. Moreover, such research could help identify emerging trends and opportunities within the market, further positioning businesses to stay ahead of the competition in an ever-evolving industry. While this pilot study provides valuable preliminary insights, future research with a larger and more diverse sample size, as well as a quantitative approach, is essential to fully understand the complexities of consumer behavior in the motorcycle accessory market. This combination of research methods would not only validate the current findings but also provide actionable data that can help businesses thrive in a competitive landscape.